If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 + x + 6 = 180 Reorder the terms: 56 + 6 + x = 180 Combine like terms: 56 + 6 = 62 62 + x = 180 Solving 62 + x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-62' to each side of the equation. 62 + -62 + x = 180 + -62 Combine like terms: 62 + -62 = 0 0 + x = 180 + -62 x = 180 + -62 Combine like terms: 180 + -62 = 118 x = 118 Simplifying x = 118
| 144=x+2+x+3 | | 3x+5y=65 | | 6-6n=-6-2n | | 7t-3=2(t+1)+2 | | 3x+4x-5=37 | | -5k+3k=-4k+2 | | 15x+20y=875 | | x+-3-3=-6 | | R(x)=x(95-4x) | | x^2+3x-127=0 | | 4+a-8a=-17 | | 80+95+x+38=180 | | n*6=24+n | | 13x-5x+6-2x= | | 7(-5x+5)=0 | | 90+90+128+x=180 | | 1-5x-2x=15 | | x^2+y^2+8x+4y= | | 15(3x+1)+20(3(3x+1))-5=875 | | 6x-(5x+9)=5x-29 | | 7m-20=2m | | 110+35+x+12=180 | | 8-7r+7=1 | | -6(6x-8)+5=-36x+53 | | 3k+8-k=0 | | -3y+15=2y-10 | | x^2+57x-87=0 | | 4x=-1y+20 | | 49+90+x=180 | | y=-2x^2+x | | 4b+10(b-1)= | | 5y+4=20y-26 |